Comparison of Contouring Results for Prostate Cancer Treatment Planning Obtained by Two Different Specialists - ALSAN ÇETİN, İLKNUR; ERGELEN, RABİA (KARE PUBL, 2016)
OBJECTIVE This study is a comparison of contoured diagnostic images derived from computed tomography (CT) and magnetic resonance imaging (MRI) by both a radiation oncologist (RO) and a radiologist (R) using volumetric modulated arc therapy (VMAT) and intensity modulated radiation therapy (IMRT) techniques. METHODS CT and MRI sections of 16 patients were contoured by the RO and the R. Planning target volume (PTV) criteria assessed were conformity index (CI), homogeneity index (HI), volume covered by 98% isodose line (V 98%) and maximum dose (D max). In critical organs, 40 Gy organ area volume (V 40), 65 Gy organ area volume (V 65), and D mean criteria were evaluated. Paired samples t-test was used for statistical analysis. RESULTS PTV and critical organs were compared. MRI PTV and bladder volume drawn by R were lower. Comparison of CT images revealed IMRT plans were superior in terms of D max and CI, while V 40 and D mean values for rectum and bladder were lower in MRI-based VMAT plans. In MRI plans, IMRT was superior in terms of PTV, D max, CI, V 65, and D mean for critical organs; however, critical organs were well preserved with both planning techniques. CONCLUSION There was some difference between contouring of the R and the RO, which was reflected in the treatment plans.
Keywords: Planning techniques; prostate cancer; radiotherapy